2018
DOI: 10.1590/s1980-220x2017023703314
|View full text |Cite|
|
Sign up to set email alerts
|

Representações sociais do cuidado em saúde de pessoas em situação de rua

Abstract: Objective Identify and analyze the structure and content of the social representations of homeless people in relation to health care. Method Qualitative study, based on the structural approach of the Theory of Social Representations, conducted with homeless people, linked to two institutional shelters. To produce the data, the free-association test was used. The resulting data was processed by two software and analyzed according to the theory above. Results Seventy-two people participated in the study. The set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
11

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 10 publications
1
6
0
11
Order By: Relevance
“…According to participants, prevention is based on practices such as: using condoms, doing tests, brushing teeth, bathing, vaccination, not using drugs, among others. These findings are in agreement with research carried out with HP in the city of Salvador, Bahia, on health care and STI prevention (10) . Despite the notion of prevention exposed by HP, their vulnerability condition exposes them to risks as well as to violation of rights.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…According to participants, prevention is based on practices such as: using condoms, doing tests, brushing teeth, bathing, vaccination, not using drugs, among others. These findings are in agreement with research carried out with HP in the city of Salvador, Bahia, on health care and STI prevention (10) . Despite the notion of prevention exposed by HP, their vulnerability condition exposes them to risks as well as to violation of rights.…”
Section: Discussionsupporting
confidence: 92%
“…On the street, people struggle to meet their needs, especially when it comes to bathing and oral care, often leading them not to practice self-care, making them dirty, smelly, exposed to prejudices and turning away. This reality was evidenced in studies with HP in the cities of São Paulo and Salvador (10)(11) . Nevertheless, the social group recognizes these practices as important and seeks to perform them.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Studies point to a number of factors that can lead a person to live on the street, such as rupture of family ties, common mental disorders, lack of a family nucleus, violence, drugs, economic situation, or even the difficulty to be in the labor market (6) . Research conducted in João Pessoa-PB, scenario of this study, revealed use of drugs and alcohol, unemployment and rupture of family ties as reasons for becoming a homeless person (7) .…”
Section: Introductionmentioning
confidence: 99%